Carbon : a field manual for building designers - Kuittinen, Matti; Organschi, Alan; Ruff, Andrew (Hoboken, New Jersey : Wiley, 2022)
'The rapid increase in global carbon emissions over the past century has created a climate crisis that threatens to disrupt the world's cultural, economic, and social fabric. The building sector is responsible for well over half of the world's extraction and consumption of carbon-based material and hydrocarbon energy. If the current design and construction approach remains unchecked, and as the world's population growth continues to accelerate, the building sector's demand for raw material and energy for new construction will continue to exacerbate the atmospheric greenhouse gas concentrations.'--
Includes bibliographical references and index.
Keywords: Carbon; Construction industry; Climatic changes